A standard model of Alzheimer's disease?. Issue 5 (2nd November 2018) - Walker, Lary C.; Lynn, David G.; Chernoff, Yury O.
ABSTRACT: The recent Research Framework proposed by the US National Institute on Aging and the Alzheimer's Association (NIA-AA) recommends that Alzheimer's disease be defined by its specific biology rather than by non-specific neurodegenerative and syndromal features. By affirming markers of abnormal Aβ and tau proteins as the essential pathobiological signature of Alzheimer's disease, the Framework tacitly reinforces the amyloid (Aβ) cascade as the leading theory of Alzheimer pathogenesis. In light of recent evidence that the cascade is driven by the misfolding and templated aggregation of Aβ and tau, we believe that an empirically grounded Standard Model of Alzheimer's pathogenesis is within reach. A Standard Model can clarify and consolidate existing information, contextualize risk factors and the complex disease phenotype, identify testable hypotheses for future research, and pave the most direct path to effective prevention and treatment.